The system of preparation of the future teacher of humanities for the professional activity in multisubject learning environment - Співаковська, Євгенія Олександрівна (ScienceRise: Pedagogical Education, 2016)
The process of creation of pedagogical system of the training of future teacher-humanitarian for the professional activity in multisubject environment was grounded. The basic components of aforesaid system were characterized. The motivational component is determined as the one of node components of the system in the context of problem and specificity of the research: the analyzed fundamental native and foreign psychological and socio-pedagogical theories of motivation. The main components of the system were determined: conceptual, objective, stimulating-motivational, content, procedural-technological, correcting-effective. The effectiveness of the system must be attained under the following pedagogical conditions: formation of subject position of the future teacher-humanitarian; activation of reflexive processes at the learning interaction; the use of the methods of psychological-pedagogical influence on the effectiveness of learning interaction in PLE; the use of active and interactive methods in PLE; the use of the means of web-services Web 2.0